Penerapan Plugin Customer Relationship Management dalam Pengelolaan Bisnis - Perina, Dias (Ebiz Prima Nusa, 2022)
In a business, one of the most difficult things to do is maintain information about our customers. Therefore, it is necessary to have a strategy to overcome this, one of which is to apply the concept of Customer Relationship Management (CRM) which is a process in managing complete information about consumers in order to optimize customer loyalty. However, it is very easy because to implement it requires training and a large amount of money. Therefore, companies can implement plugins related to CRM in WordPress on their websites because these plugins are quite easy to use for any user. The purpose of this article is to discuss CRM functions, CRM components, CRM stages, benefits of CRM, and CRM plugins that can help users manage their business.